(untitled) (Indian Journal of Public Health Research & Development, 2020)
The purpose of the study was to investigate the correlation between academic stress and suicidal ideation among students. The sample of this study included 200 students from Allen Institute of Kota(Rajasthan) . 100 were IIT aspirant students and 100 were NEET aspirant students. Academic stress measured using the academic stress scale developed by Rao, and suicidal ideation measured using the suicidal ideation scale was developed by Sisodia and Bhatnagar. The result of this study showed that no significant difference in academic stress among IIT and NEET aspirant students and significant difference was found in suicidal ideation among IITand NEET aspirant students. There are several factors that can affected academic stress and suicidal ideation like parental pressure, personal relationship issues, addiction issues, competitive atmosphere etc. The study revealed the significant relationship of academic stress and suicidal ideation among students.